The mechanism of lung tissue YKL-40 promoting the interstitial transformation of alveolar epithelial cells and its effect on TGF-β1 level in mice with idiopathic pulmonary fibrosis: Mechanism of lung tissue YKL-40 on idiopathic pulmonary fibrosis - Lingling Qi,; Guangyao Peng,; Wenting Tang,; Youyou Li,; Jing Yin,; Shan Duan,; Lihu Xie,; Xiaoping Long, (Cellular and Molecular Biology, 2023)
This study aimed to investigate the mechanism of lung tissue YKL-40 promoting the interstitial transformation of alveolar epithelial cells in mice with idiopathic pulmonary fibrosis and its effect on the level of TGF-β1. For this purpose, Forty SPF SD mice were randomly divided into 4 groups. They were the blank control group (CK group), virus-negative control group (YKL-40-NC group), YKL-40 knockdown group (YKL-40-inhibitor group) and YKL-40 overexpression group (YKL-40-mimics group), respectively. The mRNA expressions of alveolar epithelial cell mesenchymal transformation-related proteins, pulmonary fibrosis-related factors and TGF-β1-related pathway proteins in the above four groups of mice were compared to determine the mechanism of the promotion of alveolar epithelial cell mesenchymal transformation by YKL-40 in the lung tissues of mice with idiopathic pulmonary fibrosis and the effect of YKL-40 on the level of TGF-β1. The results showed that in terms of lung wet/dry weight ratio, the YKL-40-NC group, YKL-40-inhibitor group and YKL-40-mimics group were significantly increased compared with the CK group (P<0.05). About YKL-40 protein expression, compared with the CK group, AOD value and YKL-40 protein expression in the YKL-40-NC group, YKL-40-inhibitor group and YKL-40-mimics group were significantly increased (P<0.05), and compared with YKL-40-NC group, The AOD value and YKL-40 protein expression in YKL-40-inhibitor group were significantly decreased, while the AOD value and YKL-40 protein expression in YKL-40-mimics group were significantly increased (P<0.05), suggesting successful lentivirus transfection. Compared with the CK group, β-catenin and E-cadherin in the alveolar epithelial cells were significantly increased, while Pro-SPC was significantly decreased (P<0.05). The mRNA expression of pulmonary fibrosis-related factors showed that compared with the CK group, the mRNA expression of vimimin and hydroxyproline was significantly increased, while the mRNA expression of E-cadherin was decreased (P<0.05). However, the mRNA expressions of vimimin and hydroxyproline in the YKL-40-inhibitor group were significantly decreased, but the mRNA expression of E-cadherin was significantly increased. Compared with CK group, the protein expressions of TGF-β1, Smad3, Smad7 and α-Sma in the CK group were significantly increased (P<0.05). The protein expressions of TGF-β1, Smad3, Smad7 and α-SMA in the YKL-40-mimics group were significantly increased, but the protein expressions of TGF-β1, Smad3, Smad7 and α-SMA in YKL-40-inhibitor group were significantly decreased (P<0.05). In general, overexpression of YKL-40 can promote the progression of pulmonary fibrosis and the interstitial transformation of alveolar epithelial cells in mice with idiopathic fibrosis.